The role of lactate on the immunomodulatory properties of the nonbacterial fraction of kefir - Iraporda, Carolina (2014)
The identification of components responsible for the bioactive properties of functional foods is of central interest in the food industry. In particular, fermented dairy products that are of a health benefit to the consumer may exert those salutary effects through the constituent microorganisms per se and/or through other bioactive components. Kefir is a beverage obtained by the fermentation of milk with kefir grains containing different lactic- and acetic-acid bacteria plus yeasts. We studied the immunomodulatory capacity of the nonbacterial fraction of kefir through approaches involving biochemistry and cell biology. Lactate, a major microbial metabolic product, was identified as the component responsible for the modulation of certain innate immune epithelial response: At the concentrations found in kefir-fermented milk, lactate inhibits the activation of intestinal epithelial cells triggered by interleukin-1β, tumor necrosis factor-α, or flagellin. Lactate treatment furthermore abrogates NF-κB signaling in the cells, whose action could be responsible for the observed modulation of the inflammatory response. These findings provide a new perspective in the analysis of the biologic properties of kefir-fermented-milk products.